Relevansi Antara Bentuk Penyajian Tari Inla Dengan Fungsinya di Masyarakat (Jurnal Seni Tari, 2020)
This inla dance is unique in that the dancers who perform this inla dance must do what they usually call "SMS" which is Smile, Singing, and Passion. Many inla dance works now do not eliminate "SMS", but add embodiments of expressions of sadness, anger, crying, evil and so on. The concept of "SMS" is intended to provide happiness and provide positive energy for the audience. The purpose of this research is to find out the development of Inla dance. In addition, it is also to find out how the Inla dance functions in society. The source of this research data was obtained from literature study, collection of documents relating to the object of research, direct observations (active participation), video observations (passive participation), interviews and other sources to obtain data in the making of this paper. In this study the author also uses a sociological perspective based on the theory of functionalism by Talcot Parsons on Social Action Systems. The function of Inla dance in society is to be able to provide positive energy from the dance that is given. The positive energy that comes from the SMS concept that is brought from each Inla dance. Inla dance also has cultures that are different from dance in general. One of them is recommended to be vegetarian. Because Inla's vision is to protect, love, and glorify life. Keywords: SMS Concept, Inla dance, dance function